Desempenho agronômico do milho em resposta à inoculação combinada com Azospirillum brasilense e Herbaspirillum seropedicae associada à adubação nitrogenada - Dartora, Janaina (2012)
The aim of this work was to evaluate the development and productivity of maize in response to combined of bacteria Azospirillum brasilense and Herbaspirillum seropedicae in association with nitrogen fertilization. The experimental design was a randomized complete block with four replications and treatments arranged in a 4x5 factorial. The first factor is from the inoculation of seeds: non-inoculated, strain of Azospirillum brasilense (Ab-V5), strain of Herbaspirillum seropedicae (SmR1) and the combination of strains (Ab-V5+SmR1); and the second factor of nitrogen (N) rates: 0, 40, 80, 120 e 160 kg ha-1 of N. Were evaluated biometric variables: basal diameter stem, plant height, shoot dry weight and leaf area; NPK content in leaves and grains; and production components: height of ear height, ear length, ear diameter, number of rows per ear, number of grains per row, weight of ear and productivity. There was no interaction between the factors under study, and was observed a positive effect of inoculation on the development and production of maize, especially with combined inoculation of strains, wich resulted in increased crop yield of 922 kg ha-1 compared to control. The application of increasing doses of N provided increased growth and productivity of maize until the dose of 160 kg ha-1 de N. Inoculation effect was observed only on the levels of N in leaf and P in grain, while the nitrogen fertilization only influenced the P content of leaf